Processing parameters influencing drug delivery from nanofibers - Toh, Chee Wee. (2010)
The diameters of nanofibers, fabricated from bioresorbable polymers Poly (L-lactic acid) (PLLA), Polycaprolactone (PCL) and Poly (lactide-co-glycolide) (PLGA) were compared to show the differences in degradation profile associated with each particular type of polymer within a comparable diameter range. The nanofibers, produced through the process of electrospinning, were degraded in phosphate buffer solution (PBS) of pH 7.4 at 37˚C, an environment which mimics conditions in the human body. The samples were then left for up to 9 weeks in incubation and were examined for changes in physical properties weekly. The rates of water absorption and weight loss were measured by means of weight measurements, molecular weight loss was measured by Size Exclusion Chromatography (SEC) and lastly surface morphological changes were observed through the use of Scanning Electron Microscopy (SEM). Results obtained showed that fibers with smaller diameters do degrade faster than thicker fibers for they have higher surface area. Water, the main degrading agent, will be easily taken up by the thin fibers and thus explains the faster degradation.